2019
DOI: 10.1186/s43019-019-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation parameters of graft maturation on second-look arthroscopy following anterior cruciate ligament reconstruction: a systematic review

Abstract: Purpose: The purpose of this systematic review was to investigate and summarize the evaluation methods of graft maturation on second-look arthroscopy following anterior cruciate ligament (ACL) reconstruction. Methods: A literature search was performed on articles before December 2017 to identify the literature that has evaluated graft maturation on second-look arthroscopy following ACL reconstruction. Only studies using human grafts, evaluating graft maturation with two or more gross findings were included. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For arthrofibrosis, symptomatic meniscal tears, and demands for ACL revision surgery, the second‐look arthroscopy may be performed earlier if requested. Two independent surgeons evaluated both AMB and PLB grafts respectively with regard to graft continuity, graft tension, and synovial coverage [41]. The outcomes of repair or leaving in situ for pre‐existing meniscal tears were also evaluated and classified as complete healing, incomplete healing, and failure to heal [42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For arthrofibrosis, symptomatic meniscal tears, and demands for ACL revision surgery, the second‐look arthroscopy may be performed earlier if requested. Two independent surgeons evaluated both AMB and PLB grafts respectively with regard to graft continuity, graft tension, and synovial coverage [41]. The outcomes of repair or leaving in situ for pre‐existing meniscal tears were also evaluated and classified as complete healing, incomplete healing, and failure to heal [42].…”
Section: Methodsmentioning
confidence: 99%
“…For arthroibrosis, symptomatic meniscal tears, and demands for ACL revision surgery, the second-look arthroscopy may be performed earlier if requested. Two independent surgeons evaluated both AMB and PLB grafts respectively with regard to graft continuity, graft tension, and synovial coverage [41].…”
Section: Second-look Arthroscopymentioning
confidence: 99%
“…The hind limb was dissected to examine graft maturation. A scoring system was devised based on parameters used at second-look arthroscopy [ 9 ]. A category for synovial sealing at the tunnel apertures was added based on a previously reported scoring system [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to second‐look arthroscopic reports comparing BTB and HT [2, 23, 31], Ahn et al found that HT showed better synovial coverage than BTB, and Mae et al demonstrated that BTB was significantly superior to HT in anatomical ACLR. Kim et al reported no significant difference between the two groups in a systematic review, although all studies reported that there was no correlation between second‐look findings and patient‐reported outcomes.…”
Section: Introductionmentioning
confidence: 99%